Fabrication of microfluidic channel of polydimethylsiloxane using X-ray lithography and its surface nanostructuring. Issue 2 (November 2022) - Mondal, Puspen; Saundarkar, Shweta; Khantwal, Nitin; Tiwari, Pragya; Srivastava, A. K.
The microfluidic devices have attracted considerable attention for their wide range of applications in healthcare, disease diagnosis, and environmental monitoring. We present the fabrication technique, surface wetting, and bonding of a polydimethylsiloxane (PDMS) microfluidic device that will be used as an electroosmotic micromixerfor biomolecules. This technique essentially requires micromold preparation and casting of PDMS. The hardened mold was fabricated on SU-8 using X-ray lithography (XRL) beamline, BL-7, Indus-2 as the synchrotron radiation source at Raja Ramanna Centre for Advanced Technology(RRCAT). The PDMS casting and thermal cross-linking was performed by spin-coating, followed by heating with specific thermocycle. This cross-linked PDMS was bonded with smooth surfaces that were treated with different reactive plasmas using a deep reactive-ion etching (DRIE) system. In a micro fluidic channel, the flow is usually a highly ordered laminar flow and due to lack of turbulence the mixing is very difficult for larger molecules such as peptides, proteins and high-molecular-weight nucleic acids. Here, we propose a microscale mixing device where active mixers are moved by external forces, such as an applied electric field. The dimensions of the fabricated device were generated through computer simulation using the finite-element based COMSOL Multiphysics 5. 4 software. The hydrophobic nature of PDMS hinders the mobility of biomolecules through the microchannel. In this work, plasma-induced surface wettability of PDMS with application of sulfur hexafluoride (SF6 ) and oxygen (O2 ) gas recipes was investigated. As a result, the SF6 plasma–treated microchannels became stable hydrophilic and exhibited an increased adhesion or reduced air-bubble trapping during filling with aqueous solutions.